Physical Activity during the Pandemic - Afriwadi (Conferences of Medical Sciences Dies Natalis, 2020)
The spread of Corona virus disease 19 (Covid-19) which has been going on since December 2019 has had a very broad impact on all walks of life. Data quoted from the official website of the World Health Organization (WHO), as of September 25, 2020, reported that there were more than 31,026,758 confirmed cases of Covid-19 worldwide, and more than 755,786 people had died with positive Covid-19 ( 1). Meanwhile in Indonesia, as monitored by the Kompas.com website, 137,468 confirmed cases of Covid-19 were reported and more than 6,071 people died. The mortality rate is estimated to be 4.416%, of which most cases involve the elderly (> 80%) (2). Seeing the reality on the ground, by not being disciplined in responding to health protocols to prevent Covid-19 transmission, this number will continue to show an increase.